(untitled) (Boletin Médico de Postgrado, 2022)
A descriptive cross-sectional investigation was carried out to evaluate the response of the cardiorespiratory system with the use of double masks in male smokers and non-smokers between 40 and 60 years old. The sample consisted of 100 people, 50 smokers and 50 non-smokers, without respiratory or cardiovascular comorbidities. The 6-minute walk test was performed measuring parameters such as heart rate (HR), respiratory rate (FR), blood pressure (BP), oxygen saturation (SatO2), and perception of fatigue and dyspnea; in addition, the average number of meters walked was determined. There was no statistical difference before, immediately and 10 minutes after the test in the parameters studied except for the distance walked with an average of 485.6 meters for smokers and 456.63 for non-smokers (p = 0.04). This study showed that the use of double face mask does not affect important physiological cardiorespiratory parameters after a submaximal exercise test.